2019
DOI: 10.2174/1568009618666180803104631
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Proteomic Drug Targets, Therapeutic Strategies and Protein - Protein Interactions in Cancer: Mechanistic View

Abstract: Protein-protein interactions (PPIs) drive major signalling cascades and play critical role in cell proliferation, apoptosis, angiogenesis and trafficking. Deregulated PPIs are implicated in multiple malignancies and represent the critical targets for treating cancer. Herein we discuss the key protein-protein interacting domains implicated in cancer notably PDZ, SH2, SH3, LIM, PTB, SAM and PH. These domains are present in numerous enzymes/kinases, growth factors, transcription factors, adaptor proteins, recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 116 publications
0
10
0
Order By: Relevance
“…Consequently, it has been suggested that all cancer cells are likely defective in some aspect of DNA repair (69,70). Protein–protein interactions are essential for most cellular functions, including but not limited to replication, transcription, mitochondrial function, apoptosis and DNA repair (19,71–74). The BER pathway can be represented as a series of coordinated and sequential DNA repair protein complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it has been suggested that all cancer cells are likely defective in some aspect of DNA repair (69,70). Protein–protein interactions are essential for most cellular functions, including but not limited to replication, transcription, mitochondrial function, apoptosis and DNA repair (19,71–74). The BER pathway can be represented as a series of coordinated and sequential DNA repair protein complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of biomedically important SLiM‐dependent interaction domains are: kinase (e.g., cancer), phosphatase (e.g., diabetes, cancer, autism), PDZ (e.g., cystic fibrosis, cancer, pain/addiction), SH2 (e.g., immunodeficiency, X‐linked agammaglobulinemia), SH3 (e.g., kidney disease), PTB (e.g., Alzheimer's disease, diabetes, and coronary heart disease), and WW (e.g., X‐linked intellectual disabilities, cancer) domains . Therefore, understanding the basic principles of SLiM‐recognition by protein domains promises to provide powerful insight into drug discovery efforts …”
Section: Introductionmentioning
confidence: 99%
“…In some of the current approaches CRISPR applications have been used in chromatin (Adli 2018 ), and targeted epigenetic regulation, precision of CRISPR to achieve large-scale functional screenings by using guided proteins with thousands of copies of sgRNA in each targeted cell to recognize genes that influence an explicit phenotype in an individual (Lino et al 2018 ). These approaches need several technical and analytical improvements, (Dar et al 2018 ) but once recognized as standard approaches, they could be powerful tools to monitor the functionality of large numbers of genes simultaneously. The specificity and in-depth details of these assays are not in scope of this article however in 2018, Dar et al ( 2018 ) and Adli ( 2018 ) have published their excellent analysis in wide range of CRISPR screening and well documented in their articles.…”
Section: The Rise Of Crispr As the Genome Engineering Applicationmentioning
confidence: 99%
“…These approaches need several technical and analytical improvements, (Dar et al 2018 ) but once recognized as standard approaches, they could be powerful tools to monitor the functionality of large numbers of genes simultaneously. The specificity and in-depth details of these assays are not in scope of this article however in 2018, Dar et al ( 2018 ) and Adli ( 2018 ) have published their excellent analysis in wide range of CRISPR screening and well documented in their articles.…”
Section: The Rise Of Crispr As the Genome Engineering Applicationmentioning
confidence: 99%
See 1 more Smart Citation